Towards identifying choice (strategies) of technologies vs vagaries on coconut for sustainable adoption – A field – oriented exercise in participatory planning and action - B. Subburaj; R. Subramanian (International Coconut Community, 2005)
Promotion of greater access to affordable choice of technologies and their prompt use for coconut productivity is necessary to sustainable development of coconut farming. The crux of the issue is; coconut growers who are aware and have the knowledge of the technologies, also seem to be reticent about adopting the package. The question therefore is; why does this happen? This research paper summons the identification of social and ecological elements that surround adoption of innovative technologies in improving coconut production and the kind of strategies for a best fit for a need-based programme of knowledge transfer, facilitating picking up a few technologies for possible adoption. A methodological prime-mover viz., Participatory Rural Appraisal, Planning and Action among coconut growers was used to walk the ‘reality-led’ and ‘technology-driven’ choices that are really acceptable and usable. Yet the farmers/neighbours appeared to be reluctant even to “talk” the “walk”. On the other hand, absence of dependable and sustainable model, lack of confidence, inadequate infrastructure and support systems, including sufficient and timely credit and constant exposure through IT seem to accelerate ‘vagaries’ on coconut for sustainable adoption. The need must, therefore be to polarize the two contrasting positions-appropriate tech-choice vs vagaries of adoption-by a suitable ‘model’ that would serve as a guide to coconut farmers.